ARTIFICIAL INTELLIGENCE IN EDUCATION: NAVIGATING THE NEXUS OF INNOVATION AND ETHICS FOR FUTURE LEARNING LANDSCAPES - Ray, Suvendu; Ray, Deb Prasad (International Journal of Research -GRANTHAALAYAH, 2024)
Artificial intelligence (AI) holds the potential to revolutionize teaching and learning methodologies, tackle some of the largest issues facing education today, and hasten the achievement of SDG 4. The revolutionary effects of artificial intelligence (AI) on education are explored in depth in this study paper. Researcher examined the possible advantages, challenges, and ethical issues related to this changing paradigm by examining the incorporation of AI technology in several educational environments. In the present study, researchers have discussed the use of AI in education, focusing on its benefits like personalized learning, data-driven insights, and accessibility. It also discussed the drawbacks, such as data privacy, biases, and ethical issues. This study has also emphasized the importance of accountability, transparency, and justice in AI algorithms. It also discusses future developments in AI-driven education, such as adaptive learning, augmented reality, and the potential of AI to address global education issues. The focus is on promoting a balanced viewpoint and addressing ethical concerns in AI-driven education. The integration of Artificial Intelligence (AI) in education is a transformative process, offering a wide range of applications from predictive analytics to personalized learning platforms. However, ethical issues like privacy, bias, and transparency must be addressed to ensure responsible AI adoption in the future.